(untitled) (American Journal of Islam and Society, 1993)
The Intemational Institute of Islamic Thought (IIIT) is pleased to sponsor this important seminar, as its topic and objectives, the nature of the issues to be raised, and the points of view represented by the scholarly participants and their papers are of vital concern to the Islamic world. Through its participation, the institute has opened a new chapter for academic activity and intellectual jihad, particularly in Arabic and Islamic cultutal circles. As the institute joins the Union of Egyptian Engineers (UEE) in this pioneering intellectual effott, it seeks to articulate its third objective as regards the reform of the methodology of Islamic thought: the Islamization of knowledge in order to build a new Islamic cultural order and lead the ummah to the most beneficial ways of overcoming its backwardness. Moreover, as the IIIT joins the UEE in this undettaking, it seeks to exonerate itself from the charge that it is biased in favor of theoretical thinking and thus insensitive to the applied sciences. While this is the impression that might be given by the institute’s publications and statements, the truth is that these are indicative only of its priorities and have nothing to do with bias. Contemporary Western thought and cultute have begun to cast their datkness over everything in a way that obliterates, or neatly so, all non- Western thought and culture by weakening established concepts and detracting from the importance of their soutces. The West has done this under the guise of academic objectivity, by endowing its own social sciences and humanities with an assumed universality that makes of their dubious disciplines not only a virtue, but the authoritative last word. In fact, however, the West’s "universality" is little more that its own selfcentetedness and the stripping of others of all vestiges of their own civilization and culture. The universality of Islam, however, is another matter entirely, for it includes and integrates every people and every culture. Yet the West, more by means of its influence than its supposed universality, insists on popularizing slogans like "knowledge for knowledge’s sake" and "art for art’s sake" in a less-than-subtle attempt to persuade others to renounce their own traditions, thought, and culture as a prelude to plunging headlong into their supposedly universal counterparts in the West. Indeed, ...